2019
DOI: 10.1021/acs.bioconjchem.9b00436
|View full text |Cite
|
Sign up to set email alerts
|

A Reactive Antibody Platform for One-Step Production of Antibody–Drug Conjugates through a Diels–Alder Reaction with Maleimide

Abstract: The normal electron-demand Diels−Alder (DA) cycloaddition is a classic transformation routinely used in synthesis; however, applications in biological systems are limited. Here, we report a spiro[2.4]hepta-4,6-diene-containing noncanonical amino acid (SCpHK) capable of efficient incorporation into antibodies and subsequent coupling with maleimide via a DA reaction. SCpHK was stable throughout protein expression in mammalian cells and enabled covalent attachment of maleimide drug-linkers yielding DA antibody− d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…In addition, Diels‐Alder functionalities enable the conjugation of bioactive components ( Figure 1 A). [ 34–36 ] In order to introduce the corresponding functionalities, the thermogelling diblock copolymer P0, with a similar degree of polymerization as described previously, [ 18 ] was partially hydrolyzed, yielding secondary amines, which are subsequently coupled with carboxylic acids (Figure 1B). Doing so, it is critical that the thermogelling properties of the polymer P0 (Figure S1, Supporting Information) are retained after modification and that the crosslinking occurs in a time period suitable for bioprinting.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Diels‐Alder functionalities enable the conjugation of bioactive components ( Figure 1 A). [ 34–36 ] In order to introduce the corresponding functionalities, the thermogelling diblock copolymer P0, with a similar degree of polymerization as described previously, [ 18 ] was partially hydrolyzed, yielding secondary amines, which are subsequently coupled with carboxylic acids (Figure 1B). Doing so, it is critical that the thermogelling properties of the polymer P0 (Figure S1, Supporting Information) are retained after modification and that the crosslinking occurs in a time period suitable for bioprinting.…”
Section: Resultsmentioning
confidence: 99%
“…To further illustrate the power of this postfunctionalization approach, we sought to broaden the process to quantitative functionalization of terminal hydroxy groups for commodity polymers. Driven by the utility of PEG-based polymers in biomaterials and the availability of maleimide-derived functional materials such as antibody–drug conjugate payload, dyes, and bioactive small molecules, we initially focused on PEG-based systems. Using N , N ′-dicyclohexylcarbodiimide (DCC) as the coupling agent, NBD-functionalized PEG was prepared from commercially available PEG monomethyl ether ( P3 , M n = 5000 g mol –1 ).…”
Section: Resultsmentioning
confidence: 99%
“…11). 166,[175][176][177] In particular, the incorporation of ncAAs bearing ketones has been widely used to construct homogenous ADCs with potent anti-tumour pharmacology. For example, Axup et al have reported the development of a tyrosyl-derived tRNA/aaRS pair from E. coli capable of incorporating p-acetylphenylalanine (pAcF) into a peptide chain in response to the amber stop codon.…”
Section: Non-canonical Amino Acidsmentioning
confidence: 99%
“…Similarly, Christie and co-workers developed cyclopentadiene-containing ncAAs, spiro [2.4]hepta-4,6-diene-lysine (SCpHK) and cyclopentadiene-lysine (CpHK), that underwent irreversible Diels-Alder cycloadditions with maleimide-modified drugs. 177 Conjugation of SCpHK-antibodies with several maleimide payloads including Val-Cit-PABC-MMAE, AZ1508 (a tubulysin), or SG3249 (a PBD dimer) produced ADCs with DARs of 2 that were shown to be potent both in vitro and in vivo (Fig. 11D).…”
Section: Non-canonical Amino Acidsmentioning
confidence: 99%